Imagery and self-efficacy in the injury context. (May 2016) - Wesch, Natasha; Callow, Nichola; Hall, Craig; Pope, J. Paige
Abstract: Objectives: To develop and test the factorial validity of an adapted version of the Athletic Injury Imagery Questionnaire (AIIQ-2: Sordoni, Hall, & Forwell, 2002). To explore the effect of an imagery intervention on self-efficacy in the sport injury context. Design: Study 1, cross-sectional; Study 2, multiple-base line. Method: In Study 1 the AIIQ-2 was adapted to include a pain management subscale. This adapted imagery questionnaire (AIIQ-3) was then administered to 291 injured athletes (M age = 28.64 years, SD = 14.30). In Study 2 using a multiple-baseline single subject design, the effects of an imagery intervention on self-efficacy prior to physiotherapy treatment of five athletes with a Type B malleolar fracture (M age = 49.50 years, SD = 16.56) was examined. A follow-up post-experimental interview explored participants' perceptions of the intervention. Results: Study 1, confirmatory factor analysis revealed evidence for the factorial validity of the AIIQ-3. Study 2, results from the multiple-base line design demonstrated that for two out of the five participants there were observable and statistically meaningful increases in task efficacy, with the same result in three out of five participants for coping efficacy. The post-interview results revealed that all intervention participants perceived the intervention to be beneficial and effective beyond the general information provided. Conclusions: The results are discussed in terms of overcoming an inherent weakness in previous injury-related imagery research and the applied implications for the time-course of rehabilitation. Highlights: Development of pain management scale for the Athletic Injury Imagery Questionnaire-2. Evidence for the factorial validity of the adapted questionnaire provided. Imagery intervention administered to injured athletes prior to commencing physiotherapy. Positive effects of imagery intervention on task and coping efficacy revealed. Future measurement and imagery-intervention related research proposed.